A controlled open clinical trial of the positive effect of a physical intervention on quality of life in schizophrenia - Cristiano, Viviane Batista; Szortyka, Michele Fonseca; Belmonte-de-Abreu, Paulo (Frontiers in Psychiatry, 2023)
Justification Schizophrenia is a severe mental disorder associated with important physical (obesity and low motor functional capacity) and metabolic (diabetes and cardiovascular diseases) changes that contribute to a more sedentary lifestyle and a low quality of life. Objective The study aimed to measure the effect of two different protocols of physical exercise [aerobic intervention (AI) versus functional intervention ([FI)] on lifestyle in schizophrenia compared with healthy sedentary subjects. Methodology A controlled clinical trial involving patients diagnosed with schizophrenia from two different locations [Hospital de Clinicas de Porto Alegre (HCPA) and Centro de Atenção Psicosocial (CAPS) in the city of Camaquã] was carried out. The patients undertook two different exercise protocols (IA: 5-min warm-up of comfortable intensity; 45 min of aerobic exercise of increasing intensity using any of the three modalities—a stationary bicycle, a treadmill, or an elliptical trainer; and 10 min of global stretching of large muscle groups; and FI: a 5 min warm-up with a stationary walk; 15 min of muscle and joint mobility exercises; 25 min of global muscle resistance exercises; and 15 min of breathing body awareness work) twice a week for 12 weeks and were compared with physically inactive healthy controls. Clinical symptoms (BPRS), life quality (SF-36), and physical activity levels (SIMPAQ) were evaluated. The significance level was p ≤ 0.05. Results The trial involved 38 individuals, of which 24 from each group performed the AI, and 14 from each group underwent the FI. This division of interventions was not randomized but was instead decided upon for convenience. The cases showed significant improvements in quality of life and lifestyle, but these differences were greater in the healthy controls. Both interventions were very beneficial, with the functional intervention tending to be more effective in the cases and the aerobic intervention more effective in the controls. Conclusion Supervised physical activity improved life quality and reduced sedentary lifestyle in adults with schizophrenia.